Spiritual Transformation of the Main Character in the Tarung Sarung Movie - Aisyah, Siti; Agung Prasongko, Wahyu; Arif Roziqin, Muhamad (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2024)
One of the current phenomenal issues being widely discussed by the public is the disbelief in the existence of God (atheism). The issue of atheism is addressed in the film